UPIN: Utilization of Pinus Fruit Extract as an Eco-Friendly Natural Dye for Textile Applications - Asa Kafatima Zahra; Salwa Nabila; Salsabila Audya; Aprilia Nurhayati; Adhya Zahratu Syita (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
The extensive use of synthetic dyes in the textile industry has caused significant environmental problems, creating an urgent need for alternative color sources derived from renewable and eco-friendly materials. This study investigates the feasibility of utilizing pine fruit extract as a natural dye for textile applications using a water-based extraction method. Pine fruits were extracted without chemical additives, and the resulting colorant was applied to natural fiber textiles using various mordants to improve color fixation. The results indicate that water extraction is effective in obtaining tannin-based pigments from pine fruits, producing stable brown color shades. The application of natural mordants improved color intensity and uniformity, while maintaining an environmentally safe production process. These findings demonstrate that pine fruit extract has strong potential as an eco-friendly natural dye and supports sustainable and zero-waste textile practices